On Intuitionistic Fuzzy Minimal Semi-preopen Set - Kareem Mnahi , Afakar (University of Thi-Qar Journal of Science, 2017)
In this paper, we introduce the concept of intuitionistic fuzzy minimal open sets on intuitionistic fuzzy topological space. We introduce the concepts of closure and interior defined by intuitionistic fuzzy minimal open set and intuitionistic fuzzy minimal closed set. We also introduce a intuitionistic fuzzy minimal semi-preopen and intuitionistic fuzzy minimal semi-preclosed. We also redefine the concepts of closure and interior by intuitionistic fuzzy minimal semi-preopen set and intuitionistic fuzzy minimal semi-preclosed set and we introduce the concept of intuitionistic fuzzy minimal semi-precontinuous .We investigate some characterizations.